Variants translating reduced expression of the beta estrogen receptor gene were associated with increased carotid intima media thickness: A cross-sectional study in late postmenopausal women. Issue 23 (11th June 2021) - Cano-Marquina, Antonio-Jorge; García-Pérez, Miguel-Ángel; Tarín, Juan J.; Maceira, Alicia M.; Cosín-Sales, Juan; Cano, Antonio
Abstract : Abstract: There is debate on the role of estrogens in modulating the risk for atherosclerosis in women. Our purpose was to investigate whether the size of the estrogenic impact was independently associated with variation of carotid intima-media thickness (IMT) in healthy late postmenopausal women. The levels of circulating estrogens have been used in previous studies but the influence of SNPs of the estrogen receptors (ER) α and β have not been investigated. We performed a crossed-sectional study of 91 women in a university hospital. We used a double approach in which, in addition to the measurement of estradiol levels by ultrasensitive methods, genetic variants (SNPs) associated with differing expression of the ER α and β genes were assessed. Multivariable analysis was used to examine the association of candidate factors with the value of IMT and plaque detection at both the carotid wall and the sinus. A genotype combination translating reduced gene expression of the ERβ was directly associated with IMT at both the carotid wall ( P = .001) and the sinus ( P = .002). Other predictors of IMT were the levels of glucose, positively associated with IMT at both the carotid wall ( P < .001) and the sinus ( P = .001), age positively associated with IMT at the sinus ( P = .003), and levels of vitamin D, positively associated with IMT at the carotid wall ( P = .04). Poorer estrogenic impact, as concordant with a SNP variant imposing reduced expression of the ERβ, was directly associated with IMT at both the carotid wall and the sinus. Glucose level, vitamin D only for the carotid wall, and age only for the sinus, also emerged as independent factors in the IMT variance. Abstract : Supplemental Digital Content is available in the text